Multiple Criteria Decision Making Penentuan Juara Lomba Roasting Kopi Menggunakan Multi-Attributive Border Approximation Area Comparison - Sintaro, Sanriomi (Jurnal Ilmiah Computer Science, 2024)
Multiple Criteria Decision Making (MCDM) is an approach used to evaluate and select alternatives based on several criteria or factors. The purpose of this study is to apply the Multi-Attributive Border Approximation Area Comparison (MABAC) method in determining the winner of the coffee roasting competition using criteria namely fragrance, flavor, aftertaste, acidity, body, sweetness, balance, and cup to profile. With the help of the MABAC method, it will make it easier for the competition committee to determine the winner of the coffee roasting competition. The ranking results using the final results of the MABAC method for rank 1 were obtained with a final score of 8,525 on behalf of participant William, rank 2 was obtained with a final score of 5,525 on behalf of participant Firman, and rank 3 was obtained with a final value of 2,525 on behalf of participant Aditya.